Ari Permana L RANCANG BANGUN ALAT PENCACAH SAMPAH PLASTIK DI INSTALASI PENGOLAHAN SAMPAH TERPADU DI BENTENG KARANG AMBON - Sesa, Soleman; Launuru, Ari Permana; Samal, Ridwan; Renyaan, Mario; Tamtelehitu, Calvin (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2025)
The problem of plastic waste is a global problem that is increasingly urgent to be resolved, including in Indonesia, in the city of Ambon. Especially at the Benteng Karang Integrated Waste Treatment Plant (IPST), plastic waste is one of the most dominant and difficult types of waste to handle. Plastic waste that is not managed properly can accumulate and cause various environmental problems, such as land and marine pollution, which ultimately damages the ecosystem and threatens the life of marine biota and the environment. Shredding plastic waste provides a variety of significant benefits, including reducing the volume of waste so that it is easier to transport and store, and making it easier to recycle. Shredded plastic pieces require less energy to melt and are easily reshaped compared to whole bottles, saving energy in the recycling process. Researchers took data directly at the research location regarding plastic waste at the Benteng Karang Integrated Waste Treatment Plant (IPST), Ambon city, data on the volume of waste entering the Integrated Waste Treatment Plant (IPST) per month in 2023-2024 in Ambon city. In one month, according to the data obtained, 5.6 tons of plastic waste. So in one day get 18.7 kilograms. The motor control system uses the DOL system. The experiment we got from chopping 1.5 kilograms of plastic waste took 43 minutes 15 seconds Keywords: Shredding plastic waste